2022
DOI: 10.3389/fvets.2022.918114
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Limosilactobacillus mucosae LM1 Enhances Immune Functions and Modulates Gut Microbiota Without Affecting the Growth Performance of Growing Pigs

Abstract: Limosilactobacillus mucosae LM1 (LM1) is previously isolated from the intestine of piglets, but its potential as a probiotic supplement has not yet been assessed in growing pigs. In this study, we analyzed the probiotic effect of LM1 on the growth performance, apparent total tract digestibility (ATTD) of nutrients, immune properties, intestinal morphology, and gut microbiota and their metabolites in growing pigs. The experiment included 145 Duroc × (Landrace × Yorkshire) pigs (average body weight: 21.21 ± 1.14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…The beneficial bacteria Lachnoclostridium can inhibit the growth of pathogenic bacteria and regulate intestinal homeostasis ( Zhang et al., 2020 ) and Peptococcus can promote butyric acid production. Our results also showed that isobutyric acid was positively correlated with Peptococcus ( Zhang et al., 2022 ). In addition, the abundance of species belonging to the Enterobacteriaceae ( unidentified_Enterobacteriaceae ) in the Gammaproteobacteria was negatively correlated with isobutyric acid.…”
Section: Discussionsupporting
confidence: 75%
“…The beneficial bacteria Lachnoclostridium can inhibit the growth of pathogenic bacteria and regulate intestinal homeostasis ( Zhang et al., 2020 ) and Peptococcus can promote butyric acid production. Our results also showed that isobutyric acid was positively correlated with Peptococcus ( Zhang et al., 2022 ). In addition, the abundance of species belonging to the Enterobacteriaceae ( unidentified_Enterobacteriaceae ) in the Gammaproteobacteria was negatively correlated with isobutyric acid.…”
Section: Discussionsupporting
confidence: 75%
“…The results for SCFA of both probiotic mixture groups presented in Table 5 will ultimately contribute to improved swine production through improved immune function and gut health, a reduction in stress, and an improvement in animal welfare (1, 28, 29, 35) (Table 5). Probiotics are known to improve growth performance and immune function by modulating the level of SCFA in the cecum of animals (1,(36)(37)(38). However, the combined effect of the digital livestock system and probiotic mixture has not been reported until now.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that regulating GM, including Genus-Peptococcus, could enhance host immune function [32,33]. Herein, we demonstrated that CD45 on HLA DR + CD4 + in the TBNK panel may be a critical moderator between Genus-Peptococcus and NSCLC.…”
Section: Discussionmentioning
confidence: 70%